100 Summer Street and 10 High Street, 1974 - Weaver, David (Tufts Archival Research Center, 2005)
Street-level view north of the Summer and High Streets intersection, which is lined to the north with buildings. 100 Summer Street is included in the center-left half of the photograph, while 10 High Street lines the right side of the photograph. A large billboard is visible between 100 Summer Street and 10 High Street. Automobiles are parked along both Summer and High Streets. 5 1/2 x 8 5/16 Photographs